Antioxidant activity of extracts of milfoil flowers and leaves - Tarun, Ekaterina I.; Kuxta, Alesya N.; Nebokatkina, Anastasiya A.; Kurchenko, Vladimir P. (Journal of the Belarusian State University. Ecology, 2022)
A comparative study of the antioxidant activity (AOA) of 10 samples of milfoil flower extracts and 10 samples of milfoil leaf extracts collected in Russia and Kazakhstan was carried out. Fluorescein fluorescence intensity dependencies are obtained on the logarithm of the concentration of infant formula, from which IC50 and Amax values are graphically determined. Milfoil flowers extracts restored fluorescence of fluorescein to 76-88 % at a sample concentration of 0,11 %. IC50 values were in the range of 0,47-15,140'3 %. Milfoil leaves extracts restored fluorescence of fluorescein to 71-85 % at a sample concentration of 0,1-1 %. IC50 values were in the range of 0,53-2,63 • 10’2 %. Comparison of IC50 values of flowers and leaves of milfoil indicates a higher AOA of flower extracts. The minimum IC50 (0,47 • 10’3 %) was obtained for a sample of Asian milfoil flowers (Kemerovo) (Amax = 83 %), which indicates its maximum antioxidant activity. The maximum AOA was shown by samples of extracts of leaves of small-colored milfoil and noble milfoil, for which the minimum IC50 (0,53 • 10’2 %) value was obtained. IC50 indices (0,59 • 10’2 %) close to them were obtained for samples of leaves of caratavian and bristly milfoil. For all these four samples, high Amax values (76-82 %) were obtained. The minimum AOA was shown by samples of flowers of ordinary milfoil and leaves of Asian milfoil (Kemerovo). The difference when comparing the activity of flowers and leaves may indicate a different composition of substances that determine antioxidant properties. The place where the milfoil grows affects the qualitative and quantitative composition of antioxidant substances, which was shown by a comparison of 3 samples of the same species of milfoil - Asian, growing in different regions (Kazakhstan, Khakassia and Kemerovo).
Keywords: antioxidant activity; extracts of milfoil flowers and leaves; fluorescein